Halal Risk Priority In Food Supply Chain Manajemen Based On A Technology Perspective - Hana Catur Wahyuni; Waskito (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
Halal is a main requirement for Muslims in food selection. On the other hand, the increasing Muslim population in the world also encourages an increase in the availability of halal food. In its development, driven by technological advances, there is a risk of changes in halal food. These changes can occur in the food supply chain that involves various aspects. This study aims to identify risks based on technological aspects (technoware, humanware, infoware, orgaware). Furthermore, this study also aims to prioritize halal risk using the AHP method. The results showed that the type of transportation, cooperation, shipping schedule and supplier legality are sub criteria that are priority in arranging corrective actions in preventing halal risk.